Organic matter and pH in agricultural soil near the Quitasol dump, Abancay, Apurímac, Peru - Pérez-Campana, Braulio (2023)
The inadequate treatment of urban waste in landfills represents an environmental risk for agricultural soils where their edaphological properties can be modified. The aim of the study was to evaluate organic matter and pH in agricultural soil in front of the Quitasol dump in the city of Abancay, Apurímac, Peru. Three sampling points (PM1, PM2, PM3) of the agricultural soil where organic matter (OM) and pH were determined were selected by means of a random probability sampling. The results were: PM1 (MO = 1.69%; pH = 7.05), PM2 (MO = 1.12%; pH = 7.06) and PM3 (MO = 0.30%; pH = 7.26). The percentage of OM ranged from the medium to low range where there were statistically significant differences between the three sampling points. The pH values were on the neutral scale. It is concluded that the use value of the agricultural land near the Quitasol dump is limited according to the organic matter and the pH outside the interchangeable range of majority and minority elements for productivity.